Influence of organic compost treatment on biometric patterns and sensory attributes of fresh green beans (Phaseolus vulgaris L.) - Rodriguez Espinoza, Ronald Fernando (2023)
Organic production is nowadays more important for the care of the environment. Therefore, fresh horticultural products such as green beans produced with organic compost are healthier and are influenced by their sensory characteristics. The objective of this research was to evaluate the effect of organic compost on the biometric characteristics of fruits and leaves, texture, and sensory attributes of fresh green beans (Phaseolus vulgaris L.), as assessed by consumers. A completely randomized design (CRD) with five experimental treatments with different levels of organic compost was used. The results show the direct influence of the level of organic compost concentration on foliar characteristics, as the concentration of compost increases, its chemical properties are increased. However, there is no direct influence on biometric, firmness, physical-chemical, and color characteristics. The Sorting Task test according to sensory attributes shown with descriptors allows the identification of four groups: the first one formed by T1, second by T2, third by T3, and fourth by T4 and T5; while the Flash Profile test shows the formation of three groups: the first one formed by samples T1 and T2, the second T3 and the third one formed by T4 and T5. The sensory tests allowed finding similarities and differences between the green beans by consensus according to the consumers’ perception.